LINGVOKULTUROLOGIYALÍQ KOD TÚSINIGINIŃ MAZMUNÍ - Joldasbaeva, Ramuza Jaqsıbay qızı (SCIENCE and SOCIETY, 2026)
This article examines the content of the concept of linguocultural code, its theoretical foundations, and the interrelation between language and culture. The research is conducted within the framework of the anthropocentric paradigm, where the linguocultural code is interpreted as a system of linguistic means that store and transmit cultural information. The paper highlights the semiotic nature of the code, its historical development, and its role in modern linguocultural studies.